APPLICATION CITIZEN’S CHARTER IN IMPROVING THE QUALITY OF POLRI PUBLIC SERVICES - Harianja, Marasi Kindly; Tafalas, Muh Guzali; Sudarmo, Agnes Puspitasari (Awang Long Law Review, 2024)
Improving the quality of service requires support from all groups, including the integrity and commitment of the Police leadership and service officers as well as the community's commitment not to commit deviations in accordance with the Citizen's Charter (service contract) which has been formulated and established as a guideline for the implementation of Polri's public services. The public must always prioritize equal rights and justice regarding these services so that improvements in the quality of Polri's public services in the future can be achieved effectively and efficiently by achieving good governance which is characterized by clean governance. This is in accordance with the general principles of state administration (the general principle of organizational state) which consist of legal certainty, orderly state administration, public interest, openness, proportionality, professionalism and accountability.